Local Wisdom Policy and Islamic Education: Exploring Values in the Wiwit Padi Ceremony - Meilina; Sabran; Atika Muliyandari; Habib Anwar Al Anshori (Al-Qalam Institue, 2025)
This study examines the values of Islamic education in each stage of the Wiwit Padi Tradition. Qualitative research methods with a descriptive approach are used in this study. Data collection techniques used include interviews, observations, and documentation. To ensure the validity of the data, this study uses source and technique triangulation. Data analysis involves the stages of data condensation, data presentation, and conclusion. The results of the study indicate that there are Islamic educational values ​​that include Aqidah, which provides for belief in Allah SWT as the giver of life, Gratitude, which is reflected in the Wiwit Padi Tradition through sharing food and harvests, and Community (social) which is reflected in this tradition as a means to strengthen social relations between farmers in Purwobinangun Hamlet, which includes cooperation, discussion, and eating together. The implications of this study suggest that integrating Islamic educational values into local traditions like Wiwit Padi can foster a more profound sense of community and moral responsibility. It also emphasizes the importance of maintaining cultural practices that align with Islamic teachings, which can enhance social cohesion and character-building in rural communities.